Deaths during pregnancy, childbirth and puerperium: Exploring causes, context and evidence from Eastern India. Issue 11 (13th September 2020) - Sk, Md Illias Kanchan; Paswan, Balram; Anand, Ankit; Chowdhury, Poulomi; Naskar, Tapan Kumar
Abstract: Aim: The study was aimed to identify the specific reasons and circumstances of maternal deaths in West Bengal. Methods: The present study is a retrospective study of 317 maternal deaths, conducted between November 2013 and October 2015 at two major referral hospitals of eastern India, West Bengal. The frequencies, proportions, measures of central tendency and dispersion were used to describe the data. The data were analyzed using the statistical software spss version 20.0. ArcGIS 10.1 was also employed to show the distributional pattern of maternal deaths. Results: The overall maternal mortality ratio was estimated as 561 per 100 000 live births. Eclampsia or hypertensive disorders of pregnancy contributed to one‐third (33.1%, n = 105/317) of maternal deaths. The maternal deaths were more common (41%) among women belonging to the age group of 20–24 years and primiparous (36.9%) group. The average distance for traveling to reach the final hospital was 47.37 km. Approximately, three‐fourths (72.2%) of maternal deaths were in the post‐partum period. Half of the women (50.5%) sought medical care after 12 hrs of developing complications. The majority of the cases (80.1%) were referred and about 45% of patients had a cesarean section. Conclusion: The result suggests there was a shift in causes of maternal deaths from hemorrhage to eclampsia. Establishment of separate eclampsia units at lower‐level health facilities may be a more plausible pathway to prevent eclampsia‐related maternal deaths in West Bengal.